Reconfiguration of an Electrothermal-Arc Plasma Source for In Situ PMI Studies. (17th November 2021) - Lindquist, E. G.; Gebhart, T. E.; Elliott, D.; Garren, E. W.; He, Z.; Kafle, N.; Smith, C. D.; Thomas, C. E.; Zinkle, S. J.; Biewer, T. M.
Abstract: An electrothermal-arc plasma source (ET-Arc) has been developed to produce transient plasma heat and particle fluxes similar to those produced by edge localized modes onto divertor plasma-facing components in tokamaks. The ET-Arc utilizes a capacitive discharge to send current through a 4-mm-diameter, 9-cm-long capillary source liner. The liner material is ablated to form a high-velocity plasma jet that impacts the target downstream. With the current discharge circuit configuration, pulse lengths are 1 to 2 ms in duration and deliver heat fluxes of 0.25 to 2.1 GW m −2 . The plasma was previously characterized with optical emission spectroscopy (OES) on helium emission lines. The He I line ratios were interpreted with collisional radiative analysis to calculate ne and Te . The electron temperature and electron density ranged from Te = 1 to 5 eV and ne = 10 22 to 10 28 electrons/m 3, respectively. Recently, the vacuum configuration and target of the ET-Arc device were modified to allow greater diagnostic access for plasma-material interaction (PMI) studies and diagnostic development. The diagnostic suite included two Tektronix high-voltage probes to measure the capacitor and discharge potentials, a discharge current monitor, Edgertronic SC1 high-speed cameras to image the discharge, and a FLIR SC4000 infrared camera to estimate heat flux on the target. The system used OES for plasma characterization, but a new Thomson scattering (TS) diagnostic has been implemented. This system is an Advanced Research Projects Agency - Energy (ARPA-E)-funded, portable diagnostic package for spectroscopic measurements of ne, Te, ni, Ti, , and vi, which includes both TS and OES. Additionally, a novel digital holography (DH) surface-imaging diagnostic was implemented to measure erosion rates in situ. Results from ex situ DH characterization of stainless steel targets exposed to the ET-Arc source indicated that surface erosion of 150 nm per shot occurred and an in situ DH characterization of similar targets was planned. The arc-triggering system will be revised and optimized to better synchronize with the laser diagnostics. Details of the reconfigured ET-Arc source are reported here.